Integrated Approach to the Construction of Geological Models Based on Facies Analysis - O. S. Generalenko; I. V. Shelepov; O. E. Ermakova; I. V. Motorin; G. N. Vorobyova; D. D. Paramoshina (Georesursy, 2024)
Using an integrated approach, 3D geological and hydrodynamic models were built using the results of facies analysis. A sedimentological description of the core was carried out with the interpretation of facies, the formation of which occurred in relatively deep-water sedimentation conditions of the Achimov strata and 7 facies were identified. Based on the results of the facies interpretation of the core, petrofacial modeling were performed according to the concept of pore space connectivity, connectivity coefficients (Sf) were selected and the dependence of the permeability determination for each facies was clarified.In addition to determining facies by core, using the interpretation of lithology by logging, facies zones (A, B, C), associations of facies by area, seismic attributes (dynamic analysis), it was possible to perform a facies interpretation of logging curves (electrophations) and build facies maps for each cyclite within a large clinocyclite (formation). The geological model was built taking into account the internal structure of the formation and facies analysis, which made it possible to differentiate the formation into separate intervals with their dependences of filtration and capacitance properties.This approach provided a better match of the model to the real geological structure and laid the predictive basis for subsequent drilling purposes.